A method for in-situ electrochemical synthesis of defective reduced graphene oxide

The defective reduced graphene oxide was prepared in a three-electrode system through in-situ electrochemical synthesis method, which solved the problems of long reaction periods and large energy consumption in the existing doped carbon material preparation methods, and achieved a green and convenient preparation process and suitable environmental catalysis performance.

CN116905003BActive Publication Date: 2025-04-22NANKAI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310694781.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2025-04-22
Estimated Expiration
2043-06-13

AI Technical Summary

Technical Problem

The existing doped carbon material preparation methods have problems such as long reaction cycles, cumbersome synthesis processes and large energy consumption, which are difficult to meet the needs of green and convenient preparation.

Method used

In situ electrochemical synthesis method is used, and a porous conductive material is used as the cathode in the three-electrode system and a deoxygenated ionic liquid-graphene oxide composite solution is used as the electrolyte solution to prepare defective reduced graphene oxide through electrolytic reduction reaction.

Benefits of technology

It realizes a convenient and rapid preparation process, avoids a large amount of energy consumption, and is carried out at normal temperature and pressure, which is suitable for scientific research in the field of environmental catalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116905003B_ABST
    Figure CN116905003B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of defective graphene, and specifically relates to a method for in-situ electrochemical synthesis of defective reduced graphene oxide. The present invention adopts a three-electrode system or a two-electrode system, performs an electrolytic reduction reaction in an electrolyte of an imidazolyl ionic liquid, and prepares defective reduced graphene oxide doped with non-metallic elements on a porous conductive material. Compared with traditional doping methods, the method provided by the present invention is convenient and fast, does not require a large amount of energy, and can be carried out under safer and milder conditions (normal temperature and pressure, without toxic additives), which lays a foundation for scientific research on defective reduced graphene oxide in the field of environmental catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of defective graphene, and in particular relates to a method for in-situ electrochemical synthesis of defective reduced oxide graphene. Background Art

[0002] In recent years, metal materials have been proven to be effective catalysts for non-radical oxidation technologies, but the risk of secondary pollution caused by the leaching of toxic metal ions still exists. Metal-free carbon materials have become promising green alternatives to metal catalysts due to their biocompatibility, good conductivity, and tunable physicochemical properties. Incorporating heteroatoms into the carbon skeleton can not only cause charge redistribution and accelerate the electron transfer rate in specific areas, but also increase surface defects and active sites, which can significantly improve the catalytic performance of carbon materials.

[0003] For carbon materials, the introduction of heteroatoms into the carbon lattice can enhance the charge delocalization, thereby breaking the sp 2 The inertness of the hybrid carbon network improves the catalytic activity for non-radical oxidation. Table 1 summarizes the recent applications of doped graphene for catalytic induction 1 Related research on two non-free radical pathways for pollutant degradation: O2 and direct electron transfer (ETP).

[0004] Table 1 Catalytic induction of doped carbon materials 1 O2 and ETP

[0005]

[0006]

[0007] Nitrogen doping is one of the simplest and most promising methods to enhance the reactivity of carbon materials. Nitrogen atoms with localized unpaired electrons can: 1) increase the electron density of neighboring carbon atoms; 2) enhance the sp 2 π electron flow of the hybrid carbon network; 3) produce more functional groups and defect structures; 4) increase the surface polarity of the carbon material, which is conducive to interaction with polar compounds. In previous research work (Zhang T, Sun L, Sun X, et al. Radical and non-radical cooperative degradation in metal-free electro-Fenton based on nitrogen self-doped biochar [J]. Journal of Hazardous Materials, 2022, 435: 129063.), the applicant used coffee grounds as raw materials for pyrolysis to obtain endogenous nitrogen-doped carbon materials, and discovered for the first time that non-radicals were involved in the electrocatalytic oxygen reduction reaction (ORR) process.1 The production of O2. The experimental results show 1 The contribution rate of O2 to the degradation of tetracycline can reach 24.17%, which improves the selective oxidation of organic pollutants. Among them, the graphite N region has a stronger O2 adsorption capacity, which is the main factor in generating 1 Ye et al. (YeS, Zeng G, Tan X, et al. Nitrogen-doped biochar fiber with graphitization from Boehmeria nivea for promoted peroxymonosulfate activation and non-radical degradation pathways with enhancing electron transfer [J]. Applied Catalysis B: Environmental, 2020, 269.) prepared nitrogen-doped graphitized biochar fiber (PGBF-N) by graphitization and nitrogen doping. 2 The graphite N on the hybrid carbon has a strong electronegativity, which can attract the electrons of the neighboring carbon atoms to make them positively charged, thereby inducing a nucleophilic reaction of peroxymonosulfate (PMS) to generate 1 O2. At the same time, the enhanced degree of graphitization improves the conductivity of the carbon-based catalyst, playing a carbon bridge role for the realization of ETP. PGBF-N can effectively degrade TC in actual water bodies and has high anti-interference to coexisting organic or inorganic compounds. Duan et al. (Ren W, Xiong L, Yuan X, et al. Activation of Peroxydisulfate on Carbon Nanotubes: Electron-Transfer Mechanism [J]. Environmental Science & Technology, 2019, 53 (24): 14595-603.) first discovered that N-doped carbon nanotubes (N-CNT) can form a metastable complex with PMS, and then extract electrons from organic matter through conductive carbon tunnels to achieve direct oxidation. On this basis, Wang et al. concluded that the presence of graphite N promotes the adsorption of PMS by N-CNT to form a metastable complex, which increases the redox potential of the catalyst. When it exceeds the oxidation potential of phenol, phenol will be oxidized and degraded by ETP as an electron donor through the conductive carbon tunnel.

[0008] Similar to N, other non-metallic elements with different electronegativity (such as B, S, P, etc.) can also change the charge distribution of adjacent carbon atoms, thereby producing different doping effects. In addition, when two or more non-metallic elements are co-doped into carbon materials, more defects and electronic synergistic effects are usually generated, thereby further improving the catalytic activity of carbon-based catalysts. He et al. Dou J, Cheng J, Lu Z, et al. Biochar co-doped with nitrogen and boronswitching the free radical based peroxydisulfate activation into theelectron-transfer dominated nonradical process[J]. Applied Catalysis B: Environmental, 2022, 301 prepared a N / B co-doped biochar as a non-metallic activator for peroxydisulfate (PDS) to oxidatively degrade tetracycline. The experimental results and theoretical calculations showed that N / B co-doping synergistically promoted the transfer of tetracycline's HOMO electrons to the LUMO of the metastable biochar / PDS complex through the conductive carbon tunnel, ultimately leading to the decomposition of tetracycline, in which pyridine N and BC3 configurations may be important active sites. Compared with the original biochar / PDS system (22%), the non-radical contribution rate of the N / B co-doped biochar / PDS system increased to 59%, showing outstanding stability and selectivity.

[0009] In summary, heteroatom doping behavior can significantly improve the catalytic activity of carbon materials for the degradation of pollutants via non-radical pathways.

[0010] In recent years, reports on heteroatom doping of carbon materials have been common, and more and more scholars have conducted research on it. They have developed a variety of synthesis methods for doped carbon materials, mainly including pyrolysis, hydrothermal, chemical vapor deposition, etc.

[0011] The pyrolysis method usually places the carbon precursor and the heteroatom source in an inert gas such as Ar or N2, and decomposes and converts them at a certain high temperature, or directly places the carbon precursor in a gas such as NH3, H2S and CO2 for pyrolysis, which can dope a large number of heteroatoms into the carbon material and modify the surface. This method is simple to operate and is widely used in the preparation of doped carbon materials. However, the pyrolysis reaction takes a long time (even up to dozens of hours), consumes a lot of energy, and serious agglomeration may occur in the process, destroying the pore structure of the carbon material and causing its specific surface area to be significantly reduced.

[0012] The hydrothermal method generally involves placing a mixed solution of a carbon precursor and a heteroatom dopant into a reactor to achieve doping modification under high temperature and high pressure conditions. According to the operating temperature, the hydrothermal method can generally be divided into two categories: low-temperature hydrothermal method (temperature below 300°C) and high-temperature hydrothermal method (temperature in the range of 300-800°C). The high-temperature hydrothermal method can be used to synthesize doped carbon materials with a high degree of graphitization, which is beneficial to improving electrical conductivity and other properties. However, the disadvantages of this method are similar to those of the pyrolysis method, which is not conducive to green and low-carbon development.

[0013] Chemical vapor deposition uses the reaction between gaseous carbon precursor molecules and the surface of the insulating substrate to produce the desired deposit. This method is usually used for the doping modification of graphene and carbon nanotube materials. In this process, factors such as deposition temperature, deposition pressure and carrier gas flow rate can affect the properties of the deposit. Chemical vapor deposition does not require excessively high temperatures, and the structure of the obtained doped carbon material is more uniform and stable. However, based on the requirements of porous structure and defect sites, a post-processing process needs to be added. Therefore, the preparation method is relatively complicated and time-consuming and labor-intensive.

[0014] The preparation method of the above-mentioned doped carbon materials has the disadvantages of long reaction cycle, complicated synthesis process and high energy consumption. Therefore, it is necessary to develop a green and convenient preparation method. Summary of the invention

[0015] The purpose of the present invention is to provide a method for in-situ electrochemical synthesis of defective reduced graphene oxide. Compared with traditional doping methods, the method provided by the present invention is convenient and fast, does not require large amounts of energy consumption, and can be carried out under safer and milder conditions (normal temperature and pressure, without toxic additives), laying a foundation for scientific research on defective reduced graphene oxide in the field of environmental catalysis.

[0016] In order to achieve the above object, the present invention provides the following technical solutions:

[0017] The present invention provides a method for in-situ electrochemical synthesis of defective reduced graphene oxide, comprising the following steps:

[0018] In a three-electrode system, a porous conductive material is used as a cathode, and a deoxygenated ionic liquid-graphene oxide composite solution is used as an electrolyte to carry out an electrolytic reduction reaction to obtain defective reduced graphene oxide, wherein the defective reduced graphene oxide is loaded on the porous conductive material; the ionic liquid-graphene oxide composite solution comprises an imidazole-based ionic liquid, graphene oxide and a solvent; the solvent is water or an organic solvent; when the solvent is an organic solvent, the ionic liquid-graphene oxide composite solution also comprises an organic acid; the defective reduced graphene oxide is reduced graphene oxide doped with non-metallic elements.

[0019] The present invention provides a method for in-situ electrochemical synthesis of defective reduced graphene oxide, comprising the following steps:

[0020] Using a graphite material as an anode, a porous conductive material as a cathode, and a deoxidized acidic ionic liquid solution as an electrolyte, an electrolytic reduction reaction is carried out to obtain defective reduced graphene oxide, wherein the defective reduced graphene oxide is loaded on the porous conductive material; the acidic ionic liquid solution includes an imidazolyl tetraionic liquid and an acid solution; and the defective reduced graphene oxide is reduced graphene oxide doped with non-metallic elements.

[0021] Preferably, the imidazolyl ionic liquid includes imidazolyl fluoroborate ionic liquid and / or imidazolyl sulfonate ionic liquid.

[0022] Preferably, the imidazolyl ionic liquid includes one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluoroborate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium hexafluoroborate.

[0023] Preferably, the mass ratio of the imidazolyl ionic liquid to the graphene oxide is (1-500):1.

[0024] Preferably, the porous conductive material includes titanium foam, copper foam, nickel foam or an air electrode sheet.

[0025] Preferably, the negative overpotential of the electrolytic reduction reaction is -0.6 to -1.2V.

[0026] Preferably, the reaction time of the electrolytic reduction reaction is 1 to 30 minutes.

[0027] Preferably, the voltage of the electrolytic reduction reaction is 2 to 5V.

[0028] Preferably, after the electrolytic reduction reaction, the method further comprises: washing and drying the porous conductive material loaded with defective reduced graphene oxide in sequence; the drying is vacuum drying, the vacuum drying temperature is 60-70° C., and the time is 4-5 hours.

[0029] The present invention provides a method for in-situ electrochemical synthesis of defective reduced graphene oxide, comprising the following steps: in a three-electrode system, a porous conductive material is used as a cathode, and a deoxygenated ionic liquid-graphene oxide composite solution is used as an electrolyte to perform an electrolytic reduction reaction to obtain defective reduced graphene oxide, wherein the defective reduced graphene oxide is loaded on the porous conductive material; the ionic liquid-graphene oxide composite solution comprises an imidazole-based ionic liquid, graphene oxide and a solvent; the solvent is water or an organic solvent; when the solvent is an organic solvent, the ionic liquid-graphene oxide composite solution further comprises an organic acid; the defective reduced graphene oxide is reduced graphene oxide doped with non-metallic elements. The method provided by the present invention adopts a three-electrode body system to prepare defective reduced graphene oxide, specifically: the present invention relies on a potential difference to drive non-metallic heteroatoms (such as boron, fluorine and nitrogen, etc.) in the electrolyte to migrate into the graphene oxide structure, and simultaneously removes oxygen-containing functional groups at the edge of the graphene oxide, thereby obtaining layer-by-layer assembled defective two-dimensional reduced graphene oxide on the porous conductive material. Compared with traditional doping methods, the method provided by the present invention is convenient and fast, does not require large amounts of energy, and can be carried out under safer and milder conditions (normal temperature and pressure, without toxic additives), laying the foundation for scientific research on defective reduced graphene oxide in the field of environmental catalysis.

[0030] The present invention provides a method for in-situ electrochemical synthesis of defective reduced graphene oxide, comprising the following steps: using a graphite material as an anode, a porous conductive material as a cathode, and a deoxidized acidic ionic liquid solution as an electrolyte, and performing an electrolytic reduction reaction to obtain defective reduced graphene oxide, wherein the defective reduced graphene oxide is loaded on the porous conductive material; the acidic ionic liquid solution comprises an imidazole-based ionic liquid and an acid solution; and the defective reduced graphene oxide is reduced graphene oxide doped with non-metallic elements. The method provided by the present invention uses a graphite material as an anode and a porous conductive material as a cathode to prepare defective reduced graphene oxide, specifically: the present invention relies on the driving of an external voltage to peel off the graphite material of the anode to form a graphene oxide sheet, and the peeled graphene oxide sheet enters the electrolyte, and under the action of the external voltage, it migrates to the cathode of the porous conductive material together with the ionic liquid (containing heteroatomic boron, fluorine and nitrogen, etc.) in the electrolyte, and is assembled layer by layer on the cathode, thereby obtaining a layer-by-layer assembled defective two-dimensional reduced graphene oxide on the porous conductive material. Compared with traditional doping methods, the method provided by the present invention is convenient and fast, does not require large amounts of energy, and can be carried out under safer and milder conditions (normal temperature and pressure, without toxic additives), laying the foundation for scientific research on defective reduced graphene oxide in the field of environmental catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1This is a physical picture of the ionic liquid-graphene oxide composite solution in Example 1 of the present invention;

[0032] Figure 2 These are optical photographs and SEM photographs of defective reduced graphene oxide loaded on titanium foam in Example 1 of the present invention;

[0033] Figure 3 This is a TEM test image of the defective reduced graphene oxide loaded with titanium foam in Example 1 of the present invention;

[0034] Figure 4 This is the AFM test result of the defective reduced graphene oxide loaded on the titanium foam in Example 1 of the present invention;

[0035] Figure 5 The contact angle test result of the defective reduced graphene oxide loaded on the titanium foam in Example 1 of the present invention;

[0036] Figure 6 The SEM photos of defective reduced graphene oxide synthesized using copper foam and carbon black air cathode as substrates in Examples 2 and 3 of the present invention, respectively;

[0037] Figure 7 This is an optical photograph of defective reduced graphene oxide synthesized in Example 4 of the present invention;

[0038] Figure 8 This is a SEM photo of defective reduced graphene oxide synthesized in Example 4 of the present invention;

[0039] Fig. 9 The degradation of tetracycline in actual surface water by electron transfer of N, B, and F-doped graphene synthesized at different potentials in an anaerobic environment;

[0040] Fig.10 The effect of N, B, and F doped graphene synthesized under different potentials in an aerobic environment on the electroreduction of oxygen to produce free radicals to degrade tetracycline in actual surface water;

[0041] Fig.11 This is a graph showing the XPS test results of the products prepared in Example 1 and Example 5. DETAILED DESCRIPTION

[0042] The present invention provides a method for in-situ electrochemical synthesis of defective reduced graphene oxide, comprising the following steps:

[0043] In a three-electrode system, a porous conductive material is used as a cathode, and a deoxygenated ionic liquid-graphene oxide composite solution is used as an electrolyte to carry out an electrolytic reduction reaction to obtain defective reduced graphene oxide, wherein the defective reduced graphene oxide is loaded on the porous conductive material; the ionic liquid-graphene oxide composite solution comprises an imidazole-based ionic liquid, graphene oxide and a solvent; the solvent is water or an organic solvent; when the solvent is an organic solvent, the ionic liquid-graphene oxide composite solution also comprises an organic acid; the defective reduced graphene oxide is reduced graphene oxide doped with non-metallic elements.

[0044] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0045] The method for in-situ electrochemical synthesis of defective reduced graphene oxide provided by the present invention is carried out in a three-electrode system. In the present invention, the three-electrode system consists of a cathode, a counter electrode, a reference electrode and an electrolyte. The present invention uses a porous conductive material as a cathode, and the porous conductive material preferably includes foamed titanium, foamed copper, foamed nickel or an air electrode sheet. In the present invention, the air electrode sheet is preferably a microbial fuel cell air electrode prepared with reference to Example 1 in Chinese Patent CN102655235A. In the present invention, the counter electrode is preferably a platinum wire. The reference electrode is preferably a KCl-saturated Ag / AgCl electrode. The present invention uses a deoxygenated ionic liquid-graphene oxide composite solution as an electrolyte. The ionic liquid-graphene oxide composite solution includes an imidazolyl ionic liquid, graphene oxide and a solvent. In the present invention, the imidazolyl ionic liquid preferably includes an imidazolyl fluoroborate ionic liquid and / or an imidazolyl sulfonate ionic liquid. In the present invention, the imidazolyl fluoroborate ionic liquid preferably includes one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluoroborate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium hexafluoroborate. The solvent is water or an organic solvent. In the present invention, the water is preferably deionized water. The organic solvent is preferably a polar organic solvent, and N,N-dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO) are particularly preferred. In the present invention, when the organic solvent is an organic solvent, the present invention preferably uses N,N-dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO), and the dipole moments of the N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) are greater than 3.5D, which can ensure that the graphene oxide is well dispersed in the above two organic solvents, thereby ensuring that the electrolytic reduction reaction proceeds smoothly. In the present invention, when the solvent is preferably an organic solvent, the ionic liquid-graphene oxide composite solution preferably also includes an organic acid, and the organic acid is preferably malic acid and / or salicylic acid. In the present invention, when the solvent is specifically an organic solvent, the pH value of the ionic liquid-graphene oxide composite solution is preferably 5 to 5.5, and more preferably 5. In the present invention, the role of the organic acid is to supplement the proton source of the ionic liquid-graphene oxide composite solution. In the present invention, in the ionic liquid-graphene oxide composite solution, the mass ratio of the imidazolyl ionic liquid and the graphene oxide is preferably (1 to 500): 1, and more preferably (1 to 100): 1. The present invention has no special requirements for the amount of the organic acid, and it is sufficient to ensure that the pH value of the ionic liquid-graphene oxide composite solution is within the above range.

[0046] In the present invention, the method for preparing the ionic liquid-graphene oxide composite solution preferably comprises the following steps: dispersing graphene oxide in water, or dispersing graphene oxide in an organic solvent to obtain a graphene oxide dispersion; adding an imidazole-based ionic liquid dropwise to the graphene oxide dispersion to obtain an ionic liquid-graphene oxide composite solution. In the present invention, the dispersion is preferably carried out at room temperature; the dispersion is preferably ultrasonic dispersion, and the present invention has no special requirements for the specific implementation of the ultrasonic dispersion. In the present invention, the mass concentration of the graphene oxide dispersion is preferably 0.5 to 2 mg·mL -1 In the present invention, the dropping is preferably added dropwise. In the present invention, when the solvent is preferably an organic solvent, after the dropping is completed, the present invention preferably adds an organic acid to the mixed solution obtained after the dropping until the pH value of the mixed solution reaches the above range.

[0047] In the present invention, the deoxygenation treatment of the ionic liquid-graphene oxide composite solution preferably comprises the following steps: introducing an inert gas into the ionic liquid-graphene oxide composite solution for deoxygenation treatment. In the present invention, the inert gas is preferably nitrogen or argon. In the present invention, the flow rate of the inert gas is preferably 100 mL / min, and the aeration time of the deoxygenation treatment is preferably ≥ 20 min. The present invention has no special requirements for the specific range of aeration time, and it is sufficient to ensure that the oxygen in the ionic liquid-graphene oxide composite solution is completely removed.

[0048] The present invention has no special requirements on the method of introducing the inert gas, and it only needs to completely remove the oxygen in the ionic liquid-graphene oxide composite solution.

[0049] When the present invention adopts a three-electrode system polarity to carry out an electrolytic reduction reaction, the negative overpotential of the electrolytic reduction reaction is preferably -0.6 to -1.2V, more preferably -0.8 to -1.1V, and specifically preferably -1.0V. The reaction time of the electrolytic reduction reaction is preferably 1 to 30 minutes, more preferably 10 to 30 minutes. The electrolytic reduction reaction is preferably carried out under normal temperature and pressure conditions. In the present invention, the electrolytic reduction reaction is preferably carried out in an inert gas atmosphere, and the inert gas is preferably a flowing inert gas. The present invention preferably removes the oxygen generated at the anode by flowing inert gas.

[0050] After the present invention adopts a three-electrode system to carry out the electrolytic reduction reaction, the present invention preferably further comprises washing and drying the porous conductive material loaded with defective reduced graphene oxide in sequence. In the present invention, the washing is preferably washing with deionized water. The drying is preferably vacuum drying, and the temperature of the vacuum drying is preferably 60 to 70°C, more preferably 60°C; the time is preferably 4 to 5 hours, more preferably 4 hours. The vacuum drying is preferably carried out in a vacuum drying oven.

[0051] The method for in-situ electrochemical synthesis of defective reduced graphene oxide provided by the present invention may include the following steps:

[0052] Using a graphite material as an anode, a porous conductive material as a cathode, and a deoxidized acidic ionic liquid solution as an electrolyte, an electrolytic reduction reaction is carried out to obtain defective reduced graphene oxide, wherein the defective reduced graphene oxide is supported on the porous conductive material; the acidic ionic liquid solution includes an imidazole-based ionic liquid and an acid solution; and the defective reduced graphene oxide is reduced graphene oxide doped with a non-metallic element.

[0053] The method for in-situ electrochemical synthesis of defective reduced graphene oxide provided by the present invention is carried out in a two-electrode system, specifically using a graphite material as an anode, a porous conductive material as a cathode, and a deoxidized acidic ionic liquid solution as an electrolyte. In the present invention, the anode is preferably a graphite rod or a waste pencil lead. The present invention uses a porous conductive material as a cathode, and the porous conductive material preferably includes foamed titanium, foamed copper, foamed nickel or an air electrode sheet. In the present invention, the air electrode sheet is preferably a microbial fuel cell air electrode prepared with reference to Example 1 in Chinese Patent CN102655235A. In the present invention, the imidazolyl ionic liquid is preferably an imidazolyl fluoroborate ionic liquid. In the present invention, the imidazolyl fluoroborate ionic liquid preferably includes one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluoroborate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium hexafluoroborate. The acid solution is preferably an aqueous solution of an inorganic acid or an organic solution of an organic acid. The aqueous solution of an inorganic acid is preferably a sulfuric acid solution, and the molar concentration of the sulfuric acid solution is preferably 1 mol / L. The organic acid in the organic solution of an organic acid is preferably malic acid and / or salicylic acid, and the organic solvent is preferably N,N-dimethylformamide (DMF); the mass concentration of the organic acid solution is preferably 5 to 20 mg / mL. The purity of the imidazolyl ionic liquid is preferably 99.99%. In the present invention, the mass concentration of the imidazolyl tetrafluoroborate ionic liquid in the acidic ionic liquid solution is preferably determined according to the required heteroatom doping amount.

[0054] In the present invention, the deoxygenation treatment of the acidic ionic liquid solution preferably comprises the following steps: introducing an inert gas into the acidic ionic liquid solution for deoxygenation treatment. In the present invention, the inert gas is preferably nitrogen or argon. In the present invention, the flow rate of the inert gas is preferably 100 mL / min, and the aeration time of the deoxygenation treatment is preferably ≥ 20 min. The present invention has no special requirements for the specific range of aeration time, and it is sufficient to ensure that the oxygen in the ionic liquid-graphene oxide composite solution is completely removed.

[0055] When the present invention adopts a two-electrode system polarity for electrolytic reduction reaction, the voltage of the electrolytic reduction reaction is preferably 2 to 5V, more preferably 2.5 to 4.5V. The reaction time of the electrolytic reduction reaction is preferably 1 to 30min, more preferably 10 to 30min. The electrolytic reduction reaction is preferably carried out under normal temperature and pressure conditions. In the present invention, the electrolytic reduction reaction is preferably carried out in an inert gas atmosphere, and the inert gas is preferably a flowing inert gas. The present invention preferably removes oxygen generated at the anode by flowing inert gas.

[0056] After the present invention adopts a two-electrode system to carry out the electrolytic reduction reaction, the present invention preferably further comprises washing and drying the porous conductive material loaded with defective reduced graphene oxide in sequence. In the present invention, the washing is preferably washing with deionized water. The drying is preferably vacuum drying, and the temperature of the vacuum drying is preferably 60 to 70°C, more preferably 60°C; the time is preferably 4 to 5 hours, more preferably 4 hours. The vacuum drying is preferably carried out in a vacuum drying oven.

[0057] The defective reduced graphene oxide prepared by the three-electrode system or the two-electrode system is loaded on the surface of the pore structure of the porous conductive material. The defective reduced graphene oxide is reduced graphene oxide doped with non-metallic elements. In the present invention, the non-metallic elements doped in the defective reduced graphene oxide are all derived from imidazolyl ionic liquids. Therefore, in the present invention, the type of non-metallic element is determined according to the type of non-metallic element in the imidazolyl ionic liquid used.

[0058] In a specific embodiment of the present invention, the imidazolyl ionic liquid is preferably an imidazolyl fluoroborate ionic liquid, and the defective reduced graphene oxide is preferably reduced graphene oxide doped with N, B and F elements. The single-piece plane size of the defective reduced graphene oxide is preferably 450-453 nm. 2 , and preferably 452.8 nm 2The thickness of the nanosheet is preferably 1-1.5 nm, and more preferably 1.2 nm; the lattice spacing is preferably 0.3-0.35 nm, and more preferably 0.34 nm; and the pore size is preferably 4-5 μm. The defective reduced graphene oxide prepared by the present invention has good hydrophilicity, and the contact angle with water droplets is 21°.

[0059] The present invention can form defect structures on the basal plane and edge of graphene by doping with heteroatoms (such as N atoms, B atoms and F atoms), causing distortion of the surface electronic structure, thereby deriving a large number of active catalytic sites, achieving the purpose of strengthening the adsorption of charged reactants and accelerating the electron transfer in redox reactions. The present invention adopts an in-situ electrochemical synthesis method under mild reaction conditions (normal temperature and pressure) and very short time (within 30 minutes) required for the same doping amount, laying a foundation for scientific research on defective reduced graphene oxide in the field of environmental catalysis.

[0060] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0061] Example 1

[0062] Graphene oxide nanosheets were dissolved in deionized water and ultrasonicated at room temperature for 1 h to obtain a uniform and stable graphene oxide dispersion (mass concentration of 1 mg mL -1 ). The ionic liquid [EMIM][BF4] is added dropwise to the graphene oxide dispersion to form a uniform ionic liquid-graphene oxide composite solution (the mass ratio of the ionic liquid [EMIM][BF4] to the graphene oxide is 1:1) (the obtained ionic liquid-graphene oxide composite solution is as follows Figure 1 As shown). Nitrogen was introduced into the ionic liquid-graphene oxide composite solution at a flow rate of 100 ml / min for 20 minutes to ensure that oxygen was completely removed.

[0063] Titanium foam was used as the cathode, platinum wire as the counter electrode, and KCl-saturated Ag / AgCl electrode as the reference electrode, and in-situ reduction was performed at a negative potential of -1.0 V for 30 min. The reduced supported titanium foam sample was washed with deionized water and placed in a vacuum drying oven at 60 ° C for 4 h to obtain defective reduced graphene oxide supported on titanium foam, which was recorded as [IL-RGO] -1.0 The doping atoms of defective reduced graphene oxide are N atoms, B atoms and F atoms. The optical photos of the products are shown in Figure 2 a in the figure, SEM photos are shown in Figure 2 c in the figure, the TEM test results are as follows Figure 3 As shown in Figure 2, the AFM test results are as follows: Figure 4 As shown, the contact angle test is Figure 5 As shown. Figures 3 to 5 It can be seen that the defective reduced graphene oxide prepared by the three-electrode system in this embodiment is loaded on the surface of the pore structure of the porous conductive material. The thickness of the defective reduced graphene oxide nanosheets is 1.2 nm; the lattice spacing is 0.34 nm; and it has good hydrophilicity, and the contact angle with water droplets is 21°.

[0064] The atomic content of the defective reduced graphene oxide prepared in this example is shown in Table 2.

[0065] Table 2 Atomic content of defective reduced graphene oxide synthesized in situ electrochemically

[0066] atom C O N B F content% 69.13 19.58 4.5 3.1 1.3

[0067] Example 2

[0068] The preparation method is basically the same as that of Example 1, except that the titanium foam in Example 1 is replaced by copper foam. The SEM photo of the defective reduced graphene oxide supported on copper foam prepared in Example 2 is shown in FIG. Figure 6 As shown in the left 2 figures, Figure 6 The left picture 1 is an electron microscope photo of the copper foam before loading. Figure 6 The left 2 pictures in the figure are electron microscope pictures after loading defective reduced graphene oxide. Figure 6 It can be seen from the left 1 and left 2 figures in the figure that the defective reduced graphene oxide prepared in this embodiment is loaded on the surface of the foam copper pore structure.

[0069] Example 3

[0070] The preparation method is basically the same as that of Example 1, except that the titanium foam in Example 1 is replaced by a carbon black air cathode sheet. The SEM photo of the defective reduced graphene oxide loaded on the carbon black air cathode sheet prepared in Example 3 is shown in FIG. Figure 6 As shown in the left 4 figures, Figure 6 The third picture on the left is an electron microscope photo of the carbon black air cathode sheet before loading. Figure 6 The left 4th figure is an electron microscope photo of the defective reduced graphene oxide after loading. Figure 6 It can be seen from the left 3 and left 4 figures in the figure that the defective reduced graphene oxide prepared in this embodiment is loaded and evenly assembled on the surface of the pore structure of the carbon black air cathode sheet.

[0071] Example 4

[0072] Graphene oxide nanosheets were dissolved in N,N-dimethylformamide (DMF) and ultrasonicated for 1 h at room temperature to obtain a uniform and stable graphene oxide dispersion (mass concentration of 1 mg mL -1). The ionic liquid [EMIM][BF4] was added dropwise to the graphene oxide dispersion to form a uniform ionic liquid-graphene oxide composite solution (the mass ratio of the ionic liquid [EMIM][BF4] to the graphene oxide was 1:1), and the pH value of the ionic liquid-graphene oxide composite solution was adjusted to 5.0 with malic acid. Nitrogen was introduced into the ionic liquid-graphene oxide composite solution at a flow rate of 100 ml / min for 20 minutes to ensure that oxygen was completely removed.

[0073] Using titanium foam as cathode, platinum wire as counter electrode, and KCl-saturated Ag / AgCl electrode as reference electrode, the sample was reduced in situ at a negative potential of -1.0 V for 30 min. The reduced supported titanium foam sample was washed with deionized water and placed in a vacuum drying oven at 60°C for 4 h to obtain defective reduced graphene oxide supported on titanium foam. The doped heteroatoms of the defective reduced graphene oxide are N atoms, B atoms, and F atoms. The optical photograph of the product is shown in FIG. Figure 7 As shown in the SEM photos Figure 8 shown.

[0074] Example 5

[0075] The preparation method is basically the same as that in Example 1, except that the in-situ reduction is carried out at a negative potential of -0.6 V, -0.8 V or -1.2 V for 30 min, respectively; defective reduced graphene oxide supported on titanium foam is obtained, which is respectively denoted as [IL-RGO] -0.6 , [IL-RGO] -0.8 , [IL-RGO] -1.2 .

[0076] Comparative Example 1

[0077] Synthesis of defective reduced graphene oxide by hydrothermal method:

[0078] Take a certain amount of GO dispersion (1 mg / mL) in a beaker, add ionic liquid [EMIM][BF4] while stirring and ultrasonicating, so that the mass ratio of graphene oxide: ionic liquid is as high as 1:20, 1:100, 1:300, 1:500, transfer to the reactor after ultrasonicating for 30 minutes, and put it in an oven for hydrothermal reaction (120°C, 12h); finally, wash with deionized water, filter and vacuum freeze-dry to obtain the sample. XPS is used to characterize the atomic composition of the sample (Table 3):

[0079] Table 3 Atomic composition of defective reduced graphene oxide synthesized by hydrothermal method

[0080]

[0081]

[0082] By comparing the data in Table 2 of the product of Example 1 with the data in Table 3 of the product of Comparative Example 1, it can be seen that in Example 1, under the condition that the mass fraction of ionic liquid: graphene oxide is 1:1, the total amount of heteroatom doping in the in-situ electrochemical synthesis method within 30 minutes reaches 8.9%, while when the hydrothermal synthesis method of Comparative Example 1 is adopted, and the content of ionic liquid is increased by 20 to 500 times, the reaction time is extended to 12 hours, when GO / IL is 1 / 20, 1 / 100, 1 / 300, and 1 / 500, the total heteroatom doping amount is 4.17%, 3.85%, 6.38%, and 4.7%, respectively. This shows the high efficiency and energy-saving advantages of electrochemical synthesis of defective reduced graphene oxide.

[0083] Comparative Example 2

[0084] The preparation method is basically the same as that in Example 1, except that the ionic liquid-graphene oxide composite solution is not deoxygenated, and the ionic liquid-graphene oxide composite solution is directly used as an electrolyte, and is in situ reduced for 30 minutes at a negative potential of -0.6 V, -0.8 V, -1.0 V or -1.2 V, respectively; defective reduced graphene oxide supported on foamed titanium is obtained respectively.

[0085] Comparative Example 3

[0086] Graphene oxide nanosheets were dissolved in deionized water and ultrasonicated at room temperature for 1 h to obtain a uniform and stable graphene oxide dispersion (mass concentration of 1 mg mL -1 ). Nitrogen was introduced into the graphene oxide dispersion at a flow rate of 100 ml / min for 20 min to ensure that oxygen was completely removed.

[0087] Titanium foam was used as cathode, platinum wire as counter electrode, and KCl-saturated Ag / AgCl electrode as reference electrode, and in-situ reduction was performed at a negative potential of -1.0 V for 30 min. The supported titanium foam sample obtained by reduction was washed with deionized water and placed in a vacuum drying oven at 60 ° C for 4 h to obtain reduced graphene oxide supported on titanium foam (denoted as [RGO] -1.0 ). By comparing Example 1 with Comparative Example 3, it can be seen that in Comparative Example 3, without adding ionic liquid as a heteroatom source, only the oxygen-containing functional groups of the graphene oxide are reduced, and no heteroatom doping occurs.

[0088] Comparative Example 4

[0089] Graphene oxide nanosheets were dissolved in deionized water and ultrasonicated at room temperature for 1 h to obtain a uniform and stable graphene oxide dispersion (mass concentration of 1 mg mL -1). Without deoxygenation treatment, the graphene oxide dispersion was directly reduced at a negative potential of -1.0 V for 30 min using titanium foam as the cathode, platinum wire as the counter electrode, and KCl-saturated Ag / AgCl electrode as the reference electrode. The reduced supported titanium foam sample was washed with deionized water and placed in a vacuum drying oven at 60°C for 4 h to obtain graphene supported on titanium foam.

[0090] Comparative Example 5

[0091] The preparation method is basically the same as that of Example 1, except that the in-situ reduction is carried out at a negative potential of -1.5 V for 30 min; due to the influence of the violent water decomposition hydrogen side reaction, defective reduced graphene oxide is difficult to be synthesized on the electrode substrate.

[0092] Test Example 1

[0093] The titanium foam products loaded with defective reduced graphene oxide prepared in Examples 1, 5 and Comparative Examples 2 and 3 were used to degrade tetracycline in actual surface water. The specific degradation process was as follows: In a three-electrode system, defective reduced graphene oxide@titanium foam synthesized with different reduction potentials was used as the cathode, Pt wire was used as the anode, and 10 mg / L tetracycline solution was used as the simulated wastewater. A constant potential of -0.6 V was applied to the cathode to start degradation, and the change of tetracycline concentration over time was measured by liquid chromatography to calculate the removal rate. Fig. 9 The effect of N, B, F doped graphene (products prepared in Example 1 and Example 5) synthesized at different potentials in an anaerobic environment on the degradation of tetracycline in actual surface water through electron transfer; Fig.10 The results are shown in Table 1. The N, B, and F doped graphene synthesized under different potentials in an aerobic environment electro-reduced oxygen to produce free radicals to degrade tetracycline in actual surface water. Fig. 9 and 10 It can be seen that heteroatom-doped defective reduced graphene oxide can selectively degrade trace new pollutants through direct electron transfer pathways in anoxic water environments, and can selectively degrade trace new pollutants through direct electron transfer and singlet oxygen synergistic non-radical pathways in aerobic environments. This technology has a strong ability to resist the impact of changes in dissolved oxygen content in water during water treatment.

[0094] Test Example 2

[0095] The defective reduced graphene oxide products loaded on titanium foam prepared in Example 1 and Example 5 were characterized by XPS for the type and doping amount of heteroatoms. The test results are as follows: Fig.11 As shown, Fig.11 As shown, when the reduction potential increases from -1.0 V to -1.2 V, the doping amount of heteroatoms increases significantly.

[0096] Therefore, the present invention can flexibly and accurately control the doping behavior (doping amount) of foreign atoms by online regulating the potential difference.

[0097] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for in-situ electrochemical synthesis of defective reduced graphene oxide, characterized in that: The following steps are involved: In a three-electrode system, a porous conductive material is used as a cathode, and a deoxygenated ionic liquid-graphene oxide composite solution is used as an electrolyte to carry out an electrolytic reduction reaction to obtain defective reduced graphene oxide, wherein the defective reduced graphene oxide is loaded on the porous conductive material; the ionic liquid-graphene oxide composite solution comprises an imidazole-based ionic liquid, graphene oxide and a solvent; the solvent is water or an organic solvent; when the solvent is an organic solvent, the ionic liquid-graphene oxide composite solution also comprises an organic acid; the defective reduced graphene oxide is reduced graphene oxide doped with non-metallic elements.

2. A method for in-situ electrochemical synthesis of defective reduced graphene oxide, characterized in that: The following steps are involved: Using a graphite material as an anode, a porous conductive material as a cathode, and a deoxidized acidic ionic liquid solution as an electrolyte, an electrolytic reduction reaction is carried out to obtain defective reduced graphene oxide, wherein the defective reduced graphene oxide is supported on the porous conductive material; the acidic ionic liquid solution includes an imidazole-based ionic liquid and an acid solution; and the defective reduced graphene oxide is reduced graphene oxide doped with a non-metallic element.

3. The method according to claim 1 or 2, characterized in that: The imidazolyl ionic liquid includes an imidazolyl fluoroborate ionic liquid and / or an imidazolyl sulfonate ionic liquid.

4. The method according to claim 3, characterized in that The imidazolyl ionic liquid includes one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluoroborate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium hexafluoroborate.

5. The method according to claim 1, characterized in that The mass ratio of the imidazolyl ionic liquid to the graphene oxide is (1-500):

1.

6. The method according to claim 1 or 2, characterized in that: The porous conductive material includes foamed titanium, foamed copper, foamed nickel or an air electrode sheet.

7. The method according to claim 1, characterized in that The negative overpotential of the electrolytic reduction reaction is -0.6 to -1.2V.

8. The method according to claim 6, characterized in that The reaction time of the electrolytic reduction reaction is 1 to 30 minutes.

9. The method according to claim 2, characterized in that: The voltage of the electrolytic reduction reaction is 2-5V.

10. The method according to claim 1 or 2, characterized in that: After the electrolytic reduction reaction, the method further includes: washing and drying the porous conductive material loaded with defective reduced graphene oxide in sequence; the drying is vacuum drying, the vacuum drying temperature is 60-70° C., and the time is 4-5 hours.

Citation Information

Patent Citations

  • Microbial fuel cell air cathode and preparation method thereof

    CN102655235A